Band-gap tuning of graphene by Be doping and Be, B co-doping: a DFT study. Issue 69 (29th July 2015) - Ullah, Saif; Hussain, Akhtar; Syed, WaqarAdil; Saqlain, Muhammad Adnan; Ahmad, Idrees; Leenaerts, Ortwin; Karim, Altaf
<x xml:space="preserve">Abstract</x> First-principles density functional theory (DFT) calculations were carried out to investigate the structural and electronic properties of beryllium (Be) doped and, Be with boron (B) co-doped graphene systems.